Efficacy of secondary closure technique after extraction of third molars: a meta-analysis. Issue 10 (December 2019) - Ma, Shixing; Li, Xiaole; Zhang, Aobo; Liu, Shaopeng; Zhao, Haoming; Zhao, Huaqiang
Abstract: The purpose of this study was to assess the influence of two suture methods on the postoperative complications of extraction of mandibular third molars (M3M). We searched the MEDLINE (PubMed), Cochrane Library, and Web of Science databases until 18 May 2018 for randomised controlled trials (RCT) that evaluated the influence of any suture techniques on postoperative complications after the removal of impacted M3M. Pain, facial swelling, and trismus were measured for both the early stage (2–3 days) and late stage (5–7 days) after extraction. We identified 655 records, of which five were assessed for eligibility. All trials included had a moderate risk of bias. The analysis showed that the patients whose wounds had been closed primarily had significantly more pain than those whose wounds were closed secondarily (a wedge of mucosa) during the early stage (standardised mean difference (SMD), −0.49; 95% CI −0.71 to −0.27; P < 0.0001) and the late stage (SMD −0.36; 95% CI −0.54 to −0.19; P < 0.0001) after the removal of impacted M3M. Patients whose wounds were closed secondarily had less swelling (mm) at the postoperative early stage (SMD −1.12; 95% CI −1.57 to −0.66; P < 0.00001) and late stage (SMD −0.51; 95% CI −0.68 to −0.33; P < 0.00001). There was more trismus in the primary closure group than in the secondary group during both stages. Our findings suggest that secondary closure causes less pain, facial swelling, and trismus in both early and late stages of surgical removal of impacted M3M, and therefore it improves the quality of life by reducing postoperative discomfort.